Rate of progress in non-directive counseling with two Southeast Asian Muslim student groups at the University of the Philippines - Bhatti, Ishtiyaq 1954-
This study determined the rate of progress in non-directive counseling of two Southeast Asian Muslim student groups at the University of the Philippines using the Luker Measure. It hopes to be helpful to counseling practitioners and educators, particularly those involved in counseling clients from a Muslim cultural background. The author suggested that the results be used to different colleges and universities in enhancing their understanding of international and that they may be assisted in their adjustment to culturally different student lifestyles.